A Comprehensive Comparison Between the Semi-sterile and Sterile Technique for Closed Reduction and Percutaneous Pinning of Pediatric Supracondylar Humerus Fractures - Wang, Guo-Qiang; Wang, Qing-Feng; Wang, Xiao-Dong (Frontiers in Surgery, 2020)
Background: Supracondylar humerus fracture is the most common elbow fracture in children, which often requires closed reduction and percutaneous pinning (CRPP) procedure for full recovery. In addition to the traditional sterile technique with full prep and draping, the semi-sterile technique without sterile gowns and drapes has been suggested to be a viable alternative for CRPP. Methods: Here, we performed a retrospective study over a 3-year period to comprehensively evaluate the outcomes of the semi-sterile and the sterile techniques for CRPP in supracondylar humerus fractured patients. Demographic data, fracture type, nerve injury status and the type of preparation technique (semi-sterile versus sterile) were recorded. Time of preparation and operation, costs and elbow recovery status were compared. Outcomes of the two techniques were compared with bivariate analysis. Results: In a total of 137 patients, we found that the semi-sterile technique could significantly reduce the total operation room usage time (80±13 min versus 94±12 min, 15% reduction, P<0.001) and costs of CRPP. Specifically, anesthesia and medical waste costs were reduced by 139 RMB (1736±128 versus 1875±197, 7.4% reduction, P<0.001) and 103.0 RMB (14.6 versus 117.9) per operation, respectively. At the meantime, the infection rate and recovery efficiency (89±10 versus 91±9 of the Mayo Elbow Performance Score, P=0.352) were almost unchanged as compared to the sterile technique group. Conclusions: Our study suggests that the semi-sterile technique can be used as a cost-effective alternative for CRPP in supracondylar humerus fracture and even other bone-related non-surgical approaches. Level of Evidence: The present study is a retrospective cohort study with a level III of evidence.